THE NEED FOR A JOB ORIENTATION - Henryk, NOGA (Trends in education, 2013)
Choosing a job and future educational path is a very difficult decision to be faced with by each young person. In the present, commonly called "difficult", market situation, with a big percentage of unemployment, more and more technologically oriented working conditions and job changes, it is extremely important to adjust to the reality. That is why a job counseling is becoming indispensable. Also school plays a crucial role in actively supporting students to properly choose further educational paths and a future job, to plan their future career and to inform them about their opportunities. In the study some chosen aspects of job counseling, based on selected results of personal research, were signaled.
Keywords: job counseling; education